A Critical Discourse Analysis of Business Academia on the Role and Status of the National Language - Aliya Sikandar (Journal of Education and Educational Development, 2020)
This qualitative case study is an exploration of the phenomenon of the ways in which Urdu as the national language is represented in discursive practices of senior business academia. The research design, built on Fairclough’s Critical Discourse Analysis (CDA) model (2009) is of dialectical-relational approach. The participant in this single case study is a senior member of the academia from a business school. Methodologically, the analysis trailed four stages and followed CDA’s transdisciplinary traditional methods of social practices in three semiotic categories: genre, discourse and style. Findings of the study indicated that despite strong emotional links with the national language, the participant recognized the utilitarian value of English in academic and in professional domains; additionally, his perspective was that Urdu was largely marginalized due to its perceived lack of utilitarian value. The participant also expressed the viewpoint that this social injustice was needed by the social order because the business school requires English for academic and professional purposes. The study recommends a more inclusive addition of Urdu courses in business studies.
Keywords: critical discourse analysis; en-textualzation; intertextuality; orders of discourse